New Methodology for Investigating Ejaculation Dysfunction: Measuring Intraluminal Seminal Vesicle Pressure in Rats with a Telemetric Device. (1st November 2015) - Sung, Hyun Hwan; Kim, Jung Jun; Han, Deok Hyun; Kang, Su Jeong; Chae, Mee Ree; Kim, Chul Young; Park, Jong Kwan; Lee, Sung Won
Abstract: Introduction: Ejaculation dysfunction is one of the most common male sexual disorders. Despite its prevalence and adverse impact on patients, little attention has been given to investigating ejaculation dysfunction. Aim: We introduce a new method for evaluating ejaculation dysfunction in rats with a telemetric device. Methods: A pressure transducer was surgically implanted in the seminal vesicles of 7-week-old male Sprague–Dawley rats. One week later, the rats were subcutaneously administered tamsulosin 3 μg/kg, and intra-seminal vesicle pressure (ISVP) was recorded in freely moving rats after an injection of apomorphine (80 μg/kg). Same rats repeated experiment with tamsulosin 10 μg/kg, silodosin 1 mg/kg, and normal saline with 3-day intervals. Main Outcome Measure: Sexual events were visually identified and recorded. Ejaculation was confirmed by visualization of a copulatory plug in the tip of the penis. We compared the maximal ISVP and area under the curve (AUC) of the ISVP. Results: Adequate ISVP data were easily recorded and available in 66.6% rats (10/15) over a 6-week telemetric recording period (12 recordings). The mean number of ejaculations during an inspection time of 30 minutes was 1.5 ± 0.1. The maximal ISVP values in rats receiving 3 μg/kg (30.0 ± 5.2 mm Hg) and 10 μg/kg tamsulosin (15.1 ± 1.6 mm Hg) and 1 mg/kg silodosin (12.9 ± 2.2 mm Hg) were significantly lower than that in control rats (61.4 ± 13.4 mm Hg, P < 0.05). The AUC values in rats receiving 3 μg/kg (72.7 ± 18.9 mm Hg × s) and 10 μg/kg tamsulosin (23.5 ± 6.1 mm Hg) and 1 mg/kg silodosin (23.9 ± 8.0 mm Hg) were also lower than that of control rats (162.6 ± 34.3 mm Hg, P < 0.05). Conclusions: Telemetric ISVP assessment is reliable and feasible for investigating apomorphine-induced ejaculation in rats. Tamsulosin (3 μg/kg and 10 μg/kg) and silodosin 1 mg/kg decreased the ISVP during ejaculation.